2022
DOI: 10.1111/liv.15134
|View full text |Cite
|
Sign up to set email alerts
|

Estimated glomerular filtration rate by formulas in patients with cirrhosis: An unreliable procedure

Abstract: Background & Aims: In cirrhosis, the reliability of formulas that estimate renal function, either those specifically developed in this population or the classic equations, has not been properly quantified. We studied the agreement between estimated (eGFR) and measured glomerular filtration rate (mGFR) in cirrhosis. Methods: Renal function was estimated with 56 formulas including specific equations:Glomerular Filtration Rate Assessment in Liver Disease (GRAIL), Royal Free Hospital Cirrhosis (RFHC) and Mindikogl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…All employed DBS to calculate the GFR at defined time points using contrast agents, iohexol ( n = 7) or iothalamate ( n = 1). All studies demonstrated positive findings in support of DBS sampling [ 20 , 21 , 22 , 23 , 24 , 55 , 56 , 57 ]. It was however reported in one study that patients with a low haematocrit had errors in GFR measurement when using DBS; however, the authors overcame this with the use of a dried plasma sample [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All employed DBS to calculate the GFR at defined time points using contrast agents, iohexol ( n = 7) or iothalamate ( n = 1). All studies demonstrated positive findings in support of DBS sampling [ 20 , 21 , 22 , 23 , 24 , 55 , 56 , 57 ]. It was however reported in one study that patients with a low haematocrit had errors in GFR measurement when using DBS; however, the authors overcame this with the use of a dried plasma sample [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…The reduced cost of dried biofluid microsampling is a frequently cited advantage of microsampling. A total of 10 studies (14.9%) stated that dried biofluid microsampling was cheaper relative to traditional venous blood collection [ 24 , 26 , 29 , 32 , 38 , 43 , 56 , 66 , 72 ]. This was due to reduced costs associated with sample preparation, consumables and storage at room temperature [ 24 , 32 , 56 , 72 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Iohexol has the advantages of being nontoxic (at the dose used to estimate the GFR), filtered by the glomerulus, and not reabsorbed or secreted by the tubules; it is also inexpensive compared to inulin and Cr-EDTA. However, only a few studies have assessed iohexol in compensated and noncirrhotic populations[ 7 - 9 ]. Moreover, those studies had several limitations, such as use of plasma samples only, or insufficient samples or a small collection time window.…”
Section: Introductionmentioning
confidence: 99%